2015
DOI: 10.1089/gtmb.2014.0236
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Turner Syndrome by Quantitative PCR of SHOX and VAMP7 Genes

Abstract: Turner Syndrome (TS) is an unfavorable genetic condition with a prevalence of 1:2500 in newborn girls. Prompt and effective diagnosis is very important to appropriately monitor the comorbidities. The aim of the present study was to propose a feasible and practical molecular diagnostic tool for newborn screening by quantifying the gene dosage of the SHOX, VAMP7, XIST, UBA1, and SRY genes by quantitative polymerase chain reaction (qPCR) in individuals with a diagnosis of complete X monosomy, as well as those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A second subgroup of FGR fetuses with extremely short long bones is related to a dysfunction in the Growth Hormone/Insulin Growing Factor‐1 (GH/IGF‐1) axis. It is well established that GH plays a critical role in human growth, primarily through its regulation of IGF‐1 production.…”
Section: Monogenic Disordersmentioning
confidence: 99%
“…A second subgroup of FGR fetuses with extremely short long bones is related to a dysfunction in the Growth Hormone/Insulin Growing Factor‐1 (GH/IGF‐1) axis. It is well established that GH plays a critical role in human growth, primarily through its regulation of IGF‐1 production.…”
Section: Monogenic Disordersmentioning
confidence: 99%
“…It has been proposed that loss of function of some genes, in particular SHOX, may contribute to the pathology of TS. Ibarra-Ramírez et al confirmed that SHOX and VAMP7 showed the most obvious gene dose changes in the pseudo-autosomal region of TS (6). Regarding the short stature, it has been suggested that the homeobox gene SHOX in the pseudoautosomal region is a major player, and the haplotype deficiency of this gene leads to growth disorders in TS (7,8).…”
Section: Discussionmentioning
confidence: 98%